2018
DOI: 10.1111/jog.13690
|View full text |Cite
|
Sign up to set email alerts
|

Zeylenone inhibits proliferation and promotes apoptosis in ovarian carcinoma cells via Janus kinase 2 / signal transducers and activators of transcription 3 pathways

Abstract: Zeylenone inhibited cell proliferation and promoted apoptosis in ovarian carcinoma cells. The JAK-STAT pathway was involved in this progress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Furthermore, the 5‐year overall survival of ovarian cancer was still less than 40% . For one reason, the pathogenesis of ovarian cancer is complex and unknown; For another reason, the lack of high fidelity ovarian cancer research model is another important aspect.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the 5‐year overall survival of ovarian cancer was still less than 40% . For one reason, the pathogenesis of ovarian cancer is complex and unknown; For another reason, the lack of high fidelity ovarian cancer research model is another important aspect.…”
Section: Introductionmentioning
confidence: 99%
“…In SKOV3 cells incubated with zeylenone at different concentrations (2.5, 5, and 10 μmol/L for 24 h), Janus family of tyrosine kinase (p-JAK), and signal transducer with activator of transcription (p-STAT) expression levels were reduced variously. In a dose-dependent pattern, zeylenone increased the loss of MMP, apoptosis-inducing factor (AIF), and cytochrome c. Apart from that, it increased caspase-3, Fas, Fasl, and Bax in both the mRNA and protein expression levels but decreased Bcl-2 expression level [ 28 ].…”
Section: Mechanisms With Natural Plants Compound In Ovarian Cancer Cellsmentioning
confidence: 99%
“…Zeylenone (Zey) is a natural cyclohexene oxide compound isolated from Uvaria grandiflora Roxb 6 . Since the discovery of Zey in 1997, researchers have carried out multiple studies on its manufacturing processes (synthesis/semi-synthesis), pharmacodynamics and molecular mechanism, etc, and it was considered to be an anti-tumor candidate drug with great potential [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Zeylenone (Zey) is a natural cyclohexene oxide compound isolated from Uvaria grandiora Roxb. 6 Since the discovery of Zey in 1997, researchers have carried out multiple studies on its manufacturing processes (synthesis/semi-synthesis), pharmacodynamics, molecular mechanism, etc., and it was considered to be an anti-tumor drug candidate with great potential. [7][8][9][10] Studies have shown that Zey could induce signicant cell apoptosis through a mitochondrial apoptosis pathway and inhibit the invasion and migration of gastric cancer cells.…”
Section: Introductionmentioning
confidence: 99%